Performance Implications of Ties to the Government and SOEs: A Political Embeddedness Perspective - Okhmatovskiy, Ilya (Journal of Management Studies, 2010)
abstractIn many countries governments not only regulate business activities, but also become involved in the corporate governance of individual firms through ownership and board ties. While existing studies usually focus either on benefits of political connections or on costs of government influence, a political embeddedness perspective helps us consider both advantages and constraints associated with ties to the government. In particular, firms with direct ties to the government will experience significant costs associated with government officials' involvement in the corporate governance process. In contrast, firms with ties to state‐owned enterprises (SOEs) are connected to the government indirectly and thus, while getting access to state‐owned resources, avoid costs associated with the government's interventions. This study compares the performance consequences of board and ownership ties to the government with the consequences of board and ownership ties to SOEs. I find that ties to SOEs are associated with higher profitability, while no significant differences are discovered for firms with direct ties to the government.